Peningkatan Layanan RT Melalui Sistem Informasi Administrasi Berbasis Web - Dodi Solihudin; Edi Tohidi; Abi Fajar Ahmad Fauzi; Ade Valentino (AMMA : Jurnal Pengabdian Masyarakat, 2022)
Administrative services at the neighborhood level (Rukun Tetangga/RT) are an essential component in supporting good governance within communities. However, in practice, these services are still frequently managed manually, leading to various issues such as service delays, data entry errors, and inefficiencies in documentation. This Community Service Program (PKM) aims to design and implement a web-based neighborhood administrative information system to assist RT administrators in delivering faster, more accurate, and transparent services to residents. The implementation methods include needs assessment, system design, software development, as well as training and technical assistance for both administrators and residents. The system is developed using web-based technologies (PHP, MySQL, and HTML/CSS), allowing access via computers or smartphones. Key features of the system include resident data management, automated issuance and printing of official letters, archive management, and financial and activity reporting. The implementation results indicate a significant improvement in the efficiency of RT administrative services. RT administrators are no longer burdened with manual record-keeping, and residents can access services independently from their homes. Moreover, the system supports administrative transparency, as all activities are digitally recorded and easily traceable. This program has a positive impact on digital literacy among residents and strengthens the integration of information technology with public services at the micro community level. In the future, the system is expected to be replicated in other RTs as a community-based digital transformation solution.